Provincial alcohol index and its relationship to alcohol-related harm in Thailand: implications for subnational alcohol policy development - Surasak Chaiyasong; Thaksaphon Thamarangsi (BMC, 2016)
Abstract Background The Provincial Alcohol Index (PAI) is one of the efforts to develop a composite measurement to operationalize the situation of alcohol consumption and related risk behaviors. The index offers a means for national and subnational alcohol control committees to address alcohol-related problems in their responsible jurisdiction areas. The objective of this study is to assess the relationship between PAI scores and alcohol-related problems using Thailand as an example. Methods Cross-sectional analyses of PAI scores based on the 2007 National Cigarette Smoking and Alcohol Drinking Behavior Survey (CSAD) and the National Statistical Office data were conducted. CSAD data were collected from 168,285 Thai residents aged 15 years and above in 76 provinces of Thailand (population range 180,787 to 5,716,248). The PAI scores were generated using three different methods based on five indicators: 1) prevalence of adult (≥15 years) drinkers, 2) prevalence of underage drinkers, 3) proportion of regular drinkers, 4) proportion of binge drinkers and 5) proportion of drink-drivers. Alcohol-related injuries and violent events together with provincial level covariates (age, gender, income and region) were assessed. Correlational and linear regression analyses were performed to examine the relationship between PAI scores and alcohol-related problems. Results The PAI scores generated from the three methods were significantly correlated with one another (r > 0.7, p < 0.05) and significantly related to alcohol-related problems after adjusting for the provincial level covariates. Based on the normalized method, PAI scores had a significant and positive relationship with prevalence of alcohol-related injuries (beta = 562 cases per million population, p = 0.027) and violence (beta = 451 events per million population, p = 0.013). PAI scores were highest in the north and lowest in the south of the country. Conclusions The findings of this study illustrate the relationship between the PAI and alcohol-related problems. The PAI scores can be used to benchmark the alcohol situation across jurisdiction areas. Future studies are suggested to develop a scale to measure subnational alcohol policy performances.